(untitled) (Journal of Philosophy Culture and Political Science, 2018)
Modern Kazakhstan successfully overcome the diffi culties of the transit period, sets new goals to further integration into the world economy, increasing the country’s competitiveness and improve quality of life in Kazakhstan. In these circumstances, the issues related to the administrative reform as the most important factor ensuring commitment of our society democratization and further economic growth. It should be noted that the success of administrative reform is ensure effi cient activities of public administration. At all times, the administrative reform is associated with greater risks and experiencing signifi cant internal resistance. Basic principles and directions of the administrative reform were formulated on the basis of common strategic goal of building a democratic state. Key words: administrative reform, public administration, modernization, managerial model, reforming process.